Music Affinity in Wolf-Hirschhorn Syndrome - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at Nihon University School of Medicine, Tokyo, Japan, report two patients with Wolf-Hirschhorn syndrome (WHS) who have a strong affinity for music, not previously described as a feature of this syndrome.